Seven years in Tibet - Harrer, Heinrich (London : Harper Perennial, 2005)
A landmark in travel writing, this is the incredible true story of Heinrich Harrer's escape across the Himalayas to Tibet, set against the backdrop of the Second World War.
Keywords: Tibet Autonomous Region (China) -- Social life and customs; Manners and customs; Tibet Autonomous Region. -- China